The Performance of Actively and Passively Managed Swiss Equity Funds - Manuel Ammann; Michael Steiner (Swiss Journal of Economics and Statistics, 2009)
Using a Switzerland-specific Carhart (1997) model, we study the risk-adjusted performance of actively and passively managed mutual funds investing in Swiss stocks from 1989 to 2007. We also compare the performance of actively managed funds to passively managed funds instead of comparing them to a theoretical index. For a sample of 160 funds with 13'672 monthly observations we find that active as well as passive funds significantly underperform indices on an aggregated basis. However, active large-cap funds significantly underperform and active Small-&Mid-Cap-funds significantly outperform the index. Further, we find that the average manager of an active Swiss equity fund systematically overweights small-cap, value, and low-momentum stocks. When directly comparing active to passive funds, active funds significantly underperform by -1.1% p.a. on average. While active institutional funds can almost keep up with the performance of passive funds, active retail funds cannot and drive the substantial underperformance observed for active funds. Finally, active funds perform better before the millennium than thereafter. This robust result supports the hypothesis of ongoing efficiency increases in the Swiss stock market.
Keywords: G11; G12; G14; 330; Mutual Funds; Index Funds; Carhart; Performance; Switzerland